Water rights reform: Lessons for institutional design - Bruns, Bryan Randolph; Ringler, Claudia; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2005)
Internationally there is growing understanding that water rights are important and that a lack of effective water rights systems creates major problems for the management of increasingly scarce water supplies. However, discussion of water rights has often failed to recognize the range of available institutional options, the rich diversity of lessons from experience, and the need for appropriate flexibility in adapting institutional design to dynamic local conditions. In response to these concerns, the editors and other colleagues organized an international working conference, held in Hanoi, Vietnam, in February 2003, which brought together practitioners and researchers working on water rights reform. To further share ideas on improving water rights reform, this volume presents revised versions of selected papers from the conference. The focus is on experiences with implementing water rights reform cases come from countries in six continents, and many of the authors draw on additional practical experience and research in multiple countries and regions allocation systems, contributed empirical and conceptual knowledge to the discussion.